PENERAPAN MODEL PEMBELAJARAN SETS (SCIENCE ENVIRONMENT TECHNOLOGY AND SOCIETY) UNTUK MENINGKATKAN INTERNALISASI KARAKTER SISWA KELAS XI IPA 2 SMAMUHAMMADIYAH 1 KARANGANYAR - Hanifah Nur Diana; Joko Ariyanto; Sri Dwiastuti; Muhtar Sanusi (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2018)
The purpose of this research is to improve students internalization character through the implementation of learning model SETS (Science Environment Technology and Society) in class XI IPA 2 SMA Muhammadiyah 1 Karanganyar academic year 2016/2017. This research is an action research (Classroom Action Research), was held two cycles. Each cycle consists of three stages: planning, execution and observation, and reflection. The subjects were students of class XI IPA 2 SMA Muhammadiyah 1 Karanganyar academic year 2016/2017. The data research obtained through observation, tests, self-assessment questionnaires and friends, and interviews. The validity of the data using triangulation techniques. Analysis of data using qualitative descriptive analysis techniques. The research procedures using spiral model Kemmis and Mc Taggart.Aspects of the character values of students researched were honest, disciplined, hard working, creative, independent, curious, caring environment, and responsibility. The results of attitude observation 76.9%, student self-assessment 80.8%, and friend assessment 76.5%. Student achievement scores on internalizing character prasiklus 41,3%, 60,8% the first cycle and the second cycle 78.1%.Based on these research it can be concluded that the implementation of learning models SETS (Science Environment Technology and Society) can improve the character internalizationtowards the eleventh grade students of science 2 program (XI IPA 2)at SMA Muhammadiyah 1 Karanganyar. Keywords: SETS (Environment Science Technology and Society), internalizationcharacter, character education